Do people really care less about their cats than about their dogs? A comparative study in three European countries - Sandøe, Peter; Palmer, Clare; Corr, Sandra A.; Springer, Svenja; Lund, Thomas Bøker (Frontiers in Veterinary Science, 2023)
Previous studies have shown that cat owners seem to care less about their cats than dog owners care about their dogs -both in terms of their emotional state of attachment and in their willingness to pay for services that potentially benefit the animals. One study speculated that this difference is "driven by the behavior of the pet" -that the behavior of dogs encourages care more than the behavior of cats -and therefore is a universal phenomenon. However, previous studies mostly relied on convenience sampling of owners and were undertaken in single countries. Based on responses to a questionnaire from cat and dog owners drawn from representative samples of citizens (18 to 89 years of age) in three different European countries, Denmark, Austria and the UK, we tested the degree to which owners care about their cats and dogs. We used four different measures: Lexington attachment to pets scale (LAPS), possession of pet health insurance, willingness to pay for life-saving treatment, and expectation of veterinary diagnostic and treatment options. Dog owners had higher LAPS scores in all countries. However, the difference between dog and cat owners was greater in Denmark than in Austria and the UK. More dogs than cats were insured in all three countries, but the ratio was much less skewed in favor of dogs in the UK compared to Denmark. In terms of expensive life-saving treatment, in every country, more dog owners than cat owners were willing to spend over a certain amount, but the differences were much more pronounced in Denmark compared to the UK. In Denmark and Austria, dog owners expected more veterinary treatment options to be available, but slettede: much